Juran's quality essentials : for leaders - De Feo, Joseph A.; Juran, J. M. 1904-2008 (McGraw-Hill Education, 2014)
"Dr. Juran's life work on quality--boiled down to a concise guide to creating a strong, successful, globally competitive enterprise Dr. Joseph Juran was a true visionary in the field of quality, and his words continue to inspire. One of his main mantras was "Take care of the quality, and the rest will take care of itself." This work is devoted to just that--taking care of the quality. In it, the Juran Institute team presents the leadership values, beliefs, and actions of top companies, and identifies the strategies that have resulted in measurable success. Juran's Quality Essentials offers succinct, field-tested methods applicable to any industry, from service to manufacturing, and includes realistic timetables of implementation. This unique resource describes three universal quality management methods: 1. designing innovative products and services; 2. creating breakthroughs in current performance; and 3. assuring repeatable and compliant processes. Reveals how to align quality goals and methods to a company's strategic plan Provides a transformation model and roadmap Demonstrates how executive leadership is the key to a company's quality revolution--and how to make quality happen. Filled with insider tips for staying adaptable and using a benchmark to sustain performance Shows how to apply planning, control, and improvement to quality leadership for competitive advantage "--Resumé vydavatele
Keywords: management jakosti; total quality management; quality control; příručky; handbooks and manuals